Investigation of spiritual ıntelligence levels of active football players - Oğuzhan Yüksel; Sief Addeen Ra’ed Alkafaween; Orhan Demir; Aygül Oruç; Nergiz Erdem; Kakha Shamatava; Piyami Çakto; Ayla Karakullukçu (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The aim of this study is to examine the spiritual intelligence levels of active soccer players according to various variables. A survey model was used in this quantitative study. The study group consisted of 517 football players actively playing football in the 1st Amateur League, Super Amateur League and Regional Amateur League. Snowball sampling, a non-probability sampling method, was used to collect the data. The first part of the measurement tool, which consists of two parts, includes questions prepared for the demographic information of the participants. The second part includes the "Spiritual Intelligence Scale" adapted into Turkish by Erduran-Tekin & Ekşi (2019). Independent sample test (T-test) and one-way analysis of variance (One-Way ANOVA) were applied to the data obtained. According to the results of the data analysis, Welch values were taken into consideration depending on the homogeneity assumption of the data and Tukey test, one of the Post Hoc tests, was applied as a second level test. The total score and sub-dimensions of spiritual intelligence differ statistically according to marital status, age, occupation, economic income and practicing sports. The fact that football players tell the problems they experience to the people around them (family members), the maturity that occurs in individuals with the advancement of age, the assurance and personal rights they have in the profession, having an economic income that they can feel comfortable and doing sports increase the level of spiritual intelligence.